(untitled) (Bangladesh Journal of Agricultural Research, 2017)
To improve efficiency in collecting data from field experiment on fruit attributes of pointed gourd (Patal) the sample size was studied for determining optimum sample size at Olericulture Division, Horticulture Research Centre (HRC) of Bangladesh Agricultural Research Institute (BARI) Gazipur during 2013-14. Fruit length, breadth and weight data were used to design optimum sampling plan for equal number of observations per cell. The observation on fruit length (cm), breadth (cm) and weight (gm) were taken from 7 plots/treatments at random. A randomized complete block design (RCBD) with 2 replications and seven treatments/varieties were used in this experiment. A sampling plan of selecting 3 plants at random and measuring 9 fruits per selected plant (27 fruits per plot and plots were 5m2 i.e. 2.5m long and 2m wide) was found to be optimum and economy for the measurement of fruit attributes of pointed gourd. It saves time required for constant vigilance opening of flower and subsequent observations. Bangladesh J. Agril. Res. 42(2): 301-307, June 2017